Pengaruh Implementasi Sistem Informasi Manajemen Keuangan Daerah (Simda), Kualitas Sumber Daya Manusia, Dan Penerapan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Daerah (Penelitian pada Pemerintah Kabupaten Tegal) - Ulfiati, Nur, Fauzan, S.E., M.Si., Akt., CA (2017)
This study aims to determine the effect of implementation of local financial management information system (SIMDA), human resources (HR), and the application of government's accounting standards (SAP) on the quality of Tegal regency government's financial reporting. Technique of sample using purposive sampling technique with numbers of respondents as many as 54 people from 40 regional work units (SKPD) in Tegal regency. The data used are primary data. Methods of data collection is done by questionnaire. Data analysis technique is using multiple linear regression analysis by using SPSS version 21. Results showed that, 1) the implementation SIMDA affect the quality of Tegal regency government's financial reporting, 2) quality of human resources affect the quality of Tegal regency government's financial statements, 3) implementation of government accounting standards (SAP) affect the quality of Tegal regency government's financial statements. Keywords: SIMDA implementation, quality of human resources, the implementation of SAP, the quality of local government's financial statements.